(untitled) (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
Academic stress is one of the major challenges frequently encountered by university students. It may arise from heavy coursework, performance pressure, adjustment to the campus environment, poor time management, learning difficulties, psychological factors, as well as personal and environmental problems. When unmanaged, this stress can negatively affect students’ learning motivation, mental health, and academic achievement. Individual counseling is considered an effective intervention to help students cope with such stress. Through this service, students are provided opportunities to explore their concerns in a private setting, express emotions, identify stressors, develop their potential to function optimally, and obtain solutions tailored to their needs. This study applies a library research method by reviewing and analyzing books, scientific literature, and relevant research related to individual counseling and academic stress. Findings indicate that individual counseling is effective in helping students recognize stress sources, develop adaptive coping strategies, and improve emotional regulation. Therefore, the implementation of individual counseling can serve as a strategic alternative to reducing academic stress while supporting students’ psychological well-being